2008
DOI: 10.1007/s10811-008-9334-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of seaweeds in the laying hen ration to improve the quality of n-3 fatty acid enriched eggs

Abstract: An association between dietary fish oil and decreased yolk weight and reduced sensory quality of eggs has been reported when eggs are enriched with n-3 FA from fish oil. Seaweeds are an important source of compounds that seem to increase egg weight when included in the laying hen diet. The objectives of this study were to determine the influence of the dietary seaweeds Macrocystis pyrifera, Sargassum sinicola and Enteromorpha sp. on the physical quality, lipid composition and consumer acceptability of n-3 FA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 18 publications
3
28
1
Order By: Relevance
“…These results confirm the effect at a molecular level on the lipid metabolism and agree with previously reported studies (Maeda et al 2005;Seo et al 2013). These studies also demonstrated that U. clathrata had significant effects on lipid composition of different fishes and terrestrial animal species (Nakagawa et al 1987;Nakagawa 1997;Wong et al 1999;Pengzhan et al 2003;Ortiz et al 2006;Carillo et al 2008;Ergün et al 2008). In shrimp, U. clathrata promotes the production of certain 18 carbon polyunsaturated fatty acids (PUFAs) (Kumari et al 2010), as well as favoring an increase in the content of 18:0, 18:3n3, 20:5n3 (Ortiz et al 2006;Carillo et al 2008;Peña-Rodríguez et al 2010).…”
Section: Candidate Genes Involved In the Lipid Metabolism And The Immsupporting
confidence: 91%
See 1 more Smart Citation
“…These results confirm the effect at a molecular level on the lipid metabolism and agree with previously reported studies (Maeda et al 2005;Seo et al 2013). These studies also demonstrated that U. clathrata had significant effects on lipid composition of different fishes and terrestrial animal species (Nakagawa et al 1987;Nakagawa 1997;Wong et al 1999;Pengzhan et al 2003;Ortiz et al 2006;Carillo et al 2008;Ergün et al 2008). In shrimp, U. clathrata promotes the production of certain 18 carbon polyunsaturated fatty acids (PUFAs) (Kumari et al 2010), as well as favoring an increase in the content of 18:0, 18:3n3, 20:5n3 (Ortiz et al 2006;Carillo et al 2008;Peña-Rodríguez et al 2010).…”
Section: Candidate Genes Involved In the Lipid Metabolism And The Immsupporting
confidence: 91%
“…These studies also demonstrated that U. clathrata had significant effects on lipid composition of different fishes and terrestrial animal species (Nakagawa et al 1987;Nakagawa 1997;Wong et al 1999;Pengzhan et al 2003;Ortiz et al 2006;Carillo et al 2008;Ergün et al 2008). In shrimp, U. clathrata promotes the production of certain 18 carbon polyunsaturated fatty acids (PUFAs) (Kumari et al 2010), as well as favoring an increase in the content of 18:0, 18:3n3, 20:5n3 (Ortiz et al 2006;Carillo et al 2008;Peña-Rodríguez et al 2010). In contrast, it has been demonstrated that fucoidan treatment (polysaccharide extracted from brown seaweed) affects adipogenesis in 3T3-L1 cell lines (Kim et al 2010) as it suppresses the adipocites differentiation and inhibits the expression of adipogenic transcription factors α (C / EBPAα), γ (PPARγ) and AP2.…”
Section: Candidate Genes Involved In the Lipid Metabolism And The Immmentioning
confidence: 95%
“…The most commonly used antioxidant is vitamin E. However, marine algae are an additional alternative to consider. In the poultry industry, algae have been used as a source of minerals and natural pigments as a means to reduce eggs' cholesterol content (Rodríguez et al 1995;Herber-McNeill and Van Elswyk 1998;Ramos et al 1998;Carrillo et al 1992Carrillo et al , 2002Carrillo et al , 2008. Additionally, algae are a natural source of antioxidants (Ortega et al 1993;Allen et al 2001;CasasValdez et al 2006;Yuan 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Micro-and macroalgae have similarly been tested as alternatives to fish oil and flax seed for boosting the HUFA content of hen's eggs (Carrillo et al 2008;Kassis et al 2010). …”
Section: Fatty Acidsmentioning
confidence: 99%